2005
DOI: 10.1302/0301-620x.87b4.14967
|View full text |Cite
|
Sign up to set email alerts
|

Triplate fixation

Abstract: Massive endoprostheses using a cemented intramedullary stem are widely used to allow early resumption of activity after surgery for tumours. The survival of the prosthesis varies with the anatomical site, the type of prosthesis and the mode of fixation. Revision surgery is required in many cases because of aseptic loosening. Insertion of a second cemented endoprosthesis may be difficult because of the poor quality of the remaining bone, and loosening recurs quickly. We describe a series of 14 patients with tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…There was early failure in one patient which was attributed to insufficient cortical contact points, but the implantsurvival was 86% at a mean of 99 months, highlighting the validity of extra-cortical plate fixation in patients with short residual bone stock. 15 This was an evolution of the authors' previous research using an animal model which demonstrated the incorporation of HA coated titanium plates and longerterm fixation. 14 Limitations of this study include its retrospective nature and the limited number of patients in each group, which reflects the fact that custom-made endoprostheses with short medullary stems and extra-cortical plates are rarely required, and the absence of retrieval studies to confirm the osseointegration of the plates, and that despite matching the controls, there remained differences between the groups (e.g.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…There was early failure in one patient which was attributed to insufficient cortical contact points, but the implantsurvival was 86% at a mean of 99 months, highlighting the validity of extra-cortical plate fixation in patients with short residual bone stock. 15 This was an evolution of the authors' previous research using an animal model which demonstrated the incorporation of HA coated titanium plates and longerterm fixation. 14 Limitations of this study include its retrospective nature and the limited number of patients in each group, which reflects the fact that custom-made endoprostheses with short medullary stems and extra-cortical plates are rarely required, and the absence of retrieval studies to confirm the osseointegration of the plates, and that despite matching the controls, there remained differences between the groups (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…14 This work led to the in-vivo use of extra-cortical plates, without medullary stems, with excellent short-term results in small groups of patients. [15][16][17] In order to clarify the value of short-stemmed endoprostheses with extra-cortical plates, and in the absence of previous studies, we report the outcomes of a cohort of patients who underwent limb-salvage using these endoprostheses and compared their outcomes and complications with a cohort using standard length stemmed endoprostheses without extra-cortical plates.…”
Section: Discussionmentioning
confidence: 99%